Cleaner Production Implementation in a Cocoa Processing Plant in Ecuadorian Amazon - 'eguez-Santana, Karel Di; 'on, Yannay Casas-Led; Sarduy-Pereira, Liliana B 'arbara; 'erez, Luis Ernesto Arteaga-P (Journal of Environmental Accounting and Management, 2026)
The cocoa is one of the most important crops in Ecuador, intended for export and used for chocolate production in other countries. The purpose of this study is to evaluate the feasibility of the implementation of cleaner production (CP) strategies in a cocoa processing plant of the ``Tsatsayaku" producers Association. An initial in situ diagnosis on the plant environmental performance was made, and inputs and outputs of the cocoa paste elaboration process were quantified. The intensive consumption of utilities such as water, electricity, and the generation of different waste streams were the main problems detected in the diagnosis. From this analysis, seven CP alternatives were proposed to reduce the detected problems and generate additional incomes. According to the economic and environmental analyses, the proposed CP options could increase the benefit-to-cost ratio by 0.4. Furthermore, these CP practices could reduce water consumption, solid waste generation and CO_2 emissions by 20%, 58.6% and 37.5%, respectively. This study shows that CP strategies are viable options that can improve the environmental performance of small and medium-sized national companies.